2010
DOI: 10.1073/pnas.0914980107
|View full text |Cite
|
Sign up to set email alerts
|

Two isoforms of human RNA polymerase III with specific functions in cell growth and transformation

Abstract: Transcription in eukaryotic nuclei is carried out by DNA-dependent RNA polymerases I, II, and III. Human RNA polymerase III (Pol III) transcribes small untranslated RNAs that include tRNAs, 5S RNA, U6 RNA, and some microRNAs. Increased Pol III transcription has been reported to accompany or cause cell transformation. Here we describe a Pol III subunit (RPC32β) that led to the demonstration of two human Pol III isoforms (Pol IIIα and Pol IIIβ). RPC32β-containing Pol IIIβ is ubiquitously expressed and essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
113
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(122 citation statements)
references
References 42 publications
8
113
1
Order By: Relevance
“…We identified POLR3GL during a mass spectrometry analysis of Pol III highly purified from HeLa cells, and determined that these cells contain two forms of Pol III, one containing POLR3G and the other POLR3GL, consistent with previous results (Haurie et al 2010). We show that POLR3G and POLR3G arose from a DNAbased gene duplication, probably in a common ancestor of vertebrates, and we describe the genome-wide occupancy of these two forms of Pol III in IMR90 cells, a nontransformed and nonimmortalized human cell line, as well as in normal mouse liver and mouse hepatocarcinoma cells.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…We identified POLR3GL during a mass spectrometry analysis of Pol III highly purified from HeLa cells, and determined that these cells contain two forms of Pol III, one containing POLR3G and the other POLR3GL, consistent with previous results (Haurie et al 2010). We show that POLR3G and POLR3G arose from a DNAbased gene duplication, probably in a common ancestor of vertebrates, and we describe the genome-wide occupancy of these two forms of Pol III in IMR90 cells, a nontransformed and nonimmortalized human cell line, as well as in normal mouse liver and mouse hepatocarcinoma cells.…”
supporting
confidence: 74%
“…Suppression of each isoform by siRNA suggested that POLR3GL, but not POLR3G, is essential for cell survival. Moreover, ectopic expression of POLR3G, but not POLR3GL, leads to anchorage-independent growth in partially transformed human IMR90 fibroblasts (Haurie et al 2010). Together, these results suggest that POLR3G and POLR3GL carry out different functions in the cell, but what these functions may be is unclear.…”
mentioning
confidence: 64%
See 3 more Smart Citations